1998
DOI: 10.1038/sj.bmt.1701273
|View full text |Cite
|
Sign up to set email alerts
|

CD34+/CD41a+ cells best predict platelet recovery after autologous peripheral blood stem cell transplantation

Abstract: Summary:Reliable markers for megakaryocytic reconstitution after peripheral blood stem cell transplantation (PBSCT) have not been established. To determine a convenient and reliable predictor, we measured the number of megakaryocyte progenitor cells in PBSC grafts by clonogenic and flow cytometric assays. Seventeen patients with hematological and solid malignancies were included in this study. For the clonogenic assay, we used thrombopoietin (TPO) as a growth factor to evaluate the maximum number of megakaryoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…There was a positive dose-response relationship with increasing dose of pegfilgrastim and the mean peak CFU-MK count for patients who received pegfilgrastim 18 mg was statistically significantly higher than that seen in the filgrastim group. The correlation between CD41a and CFU-MK based on our data and that of others 17 has shown that CD41a can be used as a surrogate marker. The side effect profiles of pegfilgrastim and filgrastim in this study were very similar.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…There was a positive dose-response relationship with increasing dose of pegfilgrastim and the mean peak CFU-MK count for patients who received pegfilgrastim 18 mg was statistically significantly higher than that seen in the filgrastim group. The correlation between CD41a and CFU-MK based on our data and that of others 17 has shown that CD41a can be used as a surrogate marker. The side effect profiles of pegfilgrastim and filgrastim in this study were very similar.…”
Section: Discussionmentioning
confidence: 93%
“…6,8,36 This has been shown to be directly related to the CD34 þ and CD41a þ content of the apheresis product. 17,26 Additionally, no clinically significant neutralizing Ab have been described with G-CSF 37 and it is known to have an excellent safety profile and manageable side effects. 38 Newer mobilizing agents such as AMD3100, a bicyclam compound which inhibits binding of SDF-1 to cognate receptor CXCR4 on CD34 þ stem cells, when combined with G-CSF augments mobilization, but this has not yet been shown to result in speedier platelet recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations